Impaired vascular function and repair in patients with premature coronary artery disease. (December 2015) - Brittan, Mairi; Hunter, Amanda; Boulberdaa, Mounia; Fujisawa, Takeshi; Skinner, Elizabeth M; Shah, Anoop SV; Baker, Andrew H; Mills, Nicholas L
Background: Endothelial dysfunction is central to the pathogenesis of coronary artery disease, but the role of local and circulating endothelial progenitor cells in maintaining vascular health is poorly understood. We hypothesised that impaired local and circulating vascular repair mechanisms predispose to endothelial dysfunction and the premature onset of coronary artery disease. Methods and results: Patients with premature coronary artery disease ( n  = 16) and healthy age- and sex-matched controls ( n  = 16) underwent venous occlusion plethysmography with intra-arterial infusion of acetylcholine and sodium nitroprusside. Numbers of circulating endothelial progenitor cells were directly quantified in whole blood by flow cytometry. Endothelial cells were isolated from the blood vessel wall and from peripheral blood mononuclear cells, and expanded in vitro for phenotypic and functional characterisation and analysis of microRNA expression levels. A dose-dependent increase in forearm blood flow ( p  < 0.001) was attenuated in response to the endothelial-dependent vasodilator acetylcholine in patients compared with controls ( p  = 0.03). No differences in the number of circulating endothelial progenitor cells or in the phenotype, function or microRNA expression levels of endothelial outgrowth cells isolated from blood were observed in patients and controls. Conversely, local vessel wall endothelial cells from patients had significant impairments in proliferation, adhesion and migration, and significantly reduced expression levels of microRNAs known to regulate endothelial function (miRs −10 a, −let7b, −126 and −181 b) ( p  < 0.05 for all). Conclusion: Local vessel wall derived endothelial cells, rather than circulating endothelial progenitor cells and their progeny, are impaired in patients with vascular dysfunction and premature coronary artery disease.